Management Information System For Telecommunication Tower Fee Payment At The Department Of Communication And Informatics Of Mempawah Regency - Ananda, Devi Rizki Dwi; Kurniawan, Rahadian (Journal of Social Research, 2023)
The development of telecommunications technology, such as BTS towers, has provided significant benefits to society. However, the Communication and Information Office (DISKOMINFO) of Mempawah District still faces challenges in managing telecommunications tower data using separate Microsoft Excel files. This causes the data retrieval process to be slow, hinders data changes, and increases the risk of errors. In order to address this problem, the Information Technology Division of DISKOMINFO Mempawah District has developed a web-based management information system to monitor and expedite the calculation of fees and the issuance of SKRD (Tower Utilization Permit). The waterfall development method was chosen to ensure a clear understanding of the system requirements before starting development, and to ensure that each phase is completed before moving on to the next phase. It is expected that the developed telecommunications tower fee payment system will support DISKOMINFO in ensuring timely fee payments, which are crucial for the development of the telecommunications industry and the overall economy.